Weed management options in drum seeded wetland rice - Gayathri.P; Jose, Nimmy; Jacob, Jyothi Sara; AK, Ambily; M, Surendran; Babu, Hani (ORYZA-An International Journal of Rice, 2024)
High labour requirement and cost for raising nursery and transplanting of the seedlings has necessitated the shift from transplanted rice to direct-seeded rice. To reduce the requirement of large quantity of seeds, incidence of pests and diseases in broadcasting and to ensure uniform seed distribution for consistent crop growth and easier maintenance, mechanization is needed in direct-seeded rice. The major constraint experienced in wet DSR is the occurrence of high weed infestation as emerging seedlings in direct-sown fields are less competitive with concurrently emerging weeds. An experiment was conducted at M. S. Swaminathan Rice Research Station, Moncompu, Kerala Agricultural University during kharif and rabi 2021-22, with eight treatments and three replications in randomised complete block design to identify suitable cost-effective agronomic management practices to enhance the productivity of drum seeded rice and to maximise its resource-use-efficiency. The results revealed wet DSR using drumseeder as a viable crop establishment method for reducing the seed requirement, cultivation time, energy, cost of cultivation, pest and disease infestation, minimise plant stress due to transplanting and sustaining yield. There was significant variation in the yield and yield attributes in drum seeding depending on the weed management strategies adopted viz., two conoweedings, post emergent herbicide application, pre followed by post emergent herbicide application, post emergent herbicide application followed by conoweeding. Post-emergence application of Chlorimuron ethyl + Metsulfuron methyl @ 0.004 kg/ha and Penoxsulam + Cyhalofop butyl @ 0.135 kg/ha as tank mix at 18 DAS followed by conoweeding at 30 DAS was found economical in drum seeding which was on par yield with broadcasted crop yield under post emergent herbicide application.